HUBUNGAN INTENSITAS KEBISINGAN DENGAN TEKANAN DARAH PADA PEKERJA BENGKEL PT. CAPELLA MEDAN DAIHATSU AMPLAS MEDAN TAHUN 2015 - junita sm; kalsum *; eka lestari mahyuni (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Noise is one physics factor of the work environtment that can affect the productivity of worker. High intensity noise also raise blood pressure and in the long term will burden the heart and caused stress that eventually lead to fatigue. The research method used analytical observation with cross sectional approach. The purpose of this study was to determine the intensity and blood pressure also determine the relationship of the intensity of the noise with a blood pressure on labour workshop PT.Capella Medan Daihatsu, Amplas, Medan. The population is all workers at PT. Capella Medan Daihatsu, Amplas, Medan, part of after sales repair body and paint service, as many as 17 people and all the population to be the sample. The result showed the mean condition of noise work environment is 97,35 dB (A). By Pearson Product Moment Correlation test indicated that the intensity of noise exposure with blood pressure obtained p value of systolic blood pressure after work = 0,002 (p≤0,05), and results of correlation test p value of diastolic after work = 0,002 (p≤0,05), and with Wilcoxon test indicated that systolic blood pressure after and before work obtained p value =0,00 (p<0,005), diastolic blood pressure after work obtained p value= 0,001 (p<0,005), indicated there is different significantly. Recommended to the company that paid more attention to the feasibility conditions and the working environment for workers to use personal protective equipment when working. Key Words: Blood pressure, Noise, Workshop workers